Pengaruh Model Pembelajaran Inkuiri Terbimbing dengan Metode Eksperimen terhadap Hasil Belajar Fisika Siswa Kelas XI IPA SMAN 2 Mataram Tahun Pelajaran 2016/2017 - Roni Wahyuni; Hikmawati Hikmawati; Muhammad Taufik (Department of Physics Education, Universitas Mataram, 2016)
This study is aimed todetermine the effect ofÃÂ guided-inqury learning model combined with the experimental method on physics learning outcomes grade XI IPA inÃÂ SMAN 2 Mataram of academic year 2016/2017. This is quasi-experimental research with pretest and posttest control group design. The population is all students grade XI IPA in SMAN 2 Mataram and the sample is student class XI IPA-7 as the experimental group and class XI IPA-9 as the control one which is selected by purposive sampling. The data of physics outcomes learning is collected by using multiple-choice test. Average value obtained in experimental class is 77.00, while in control is 65.65. The highest N-gain value is in sub material elasticity properties of material, it is 51% in controlÃÂ and 88% in experimental. Statistical used is t-test polled variance at significant level of 5% and the result obtained tcountis 6,27. This value is greater than ttable (ttable=1.993). It means that there is an influence of guided-inquiry learning model combined with the experimental method on physics learning outcomes grade XI IPA in SMAN 2 Mataram.